2021
DOI: 10.3126/nh.v15i0.36650
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Lettuce (Lactuca Sativa L.) Genotypes with Respect to Morphological, Yield and Quality Traits at Two Localities of Nepal

Abstract: Lettuce is cultivated as minor crop in Nepal. However, people are becoming more health conscious in these days and demand for salad is increasing in food.  The demand of lettuce is also gradually increasing but relatively few farmers are involved in this crop due to the lack of high-yielding and good quality genotypes. The research was conducted at two locations of Nepal; Kavre and Kaski with the aim of evaluating the performance of seven different hybrid lettuce genotypes in terms of its morphology, yield, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the same manner, the shortest leaf width (7.17cm) was observed on the variety RSK-3 at Fogera and the maximum value of leaf width (17.40cm) was recorded on Tesfa variety at Libokemkem site with the mean value of 11.4cm. Similarly, Januka et al [8] in Nepal found that leaf length and leaf width had showed a highly significant difference between locations and variety with the value of leaf length ranged from 14-25cm whereas leaf width ranged from13-20cm. Bewuket and Shewaye obtained the maximum leaf width of 11.22 cm from the variety named "Great Lake" at Wulkite university research site in Southern part of Ethiopia [16].…”
Section: Mean Performance Of Lettuce Varieties For Yield and Yield At...mentioning
confidence: 81%
See 1 more Smart Citation
“…In the same manner, the shortest leaf width (7.17cm) was observed on the variety RSK-3 at Fogera and the maximum value of leaf width (17.40cm) was recorded on Tesfa variety at Libokemkem site with the mean value of 11.4cm. Similarly, Januka et al [8] in Nepal found that leaf length and leaf width had showed a highly significant difference between locations and variety with the value of leaf length ranged from 14-25cm whereas leaf width ranged from13-20cm. Bewuket and Shewaye obtained the maximum leaf width of 11.22 cm from the variety named "Great Lake" at Wulkite university research site in Southern part of Ethiopia [16].…”
Section: Mean Performance Of Lettuce Varieties For Yield and Yield At...mentioning
confidence: 81%
“…Lettuce is produced commercially in many countries and is also widely grown as a vegetable in home gardens [9]. The main producers of lettuce in the world are the USA, Spain, Italy, Japan and, France [8].…”
Section: Introductionmentioning
confidence: 99%